2012
DOI: 10.4088/jcp.12r07694
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Induced Depression in Chronic Hepatitis C

Abstract: One in 4 chronic hepatitis C patients who start interferon and ribavirin treatment will develop an induced major depressive episode. Clinicians should attempt a full evaluation of patients before starting antiviral treatment in order to identify those at risk of developing interferon-induced depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
183
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(205 citation statements)
references
References 64 publications
15
183
4
3
Order By: Relevance
“…Finally, patients treated with proinflammatory cytokines often develop depression. Treatment with interferon-γ, in particular, is associated with depression [41].…”
Section: The Contribution Of Inflammation To Depression and Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, patients treated with proinflammatory cytokines often develop depression. Treatment with interferon-γ, in particular, is associated with depression [41].…”
Section: The Contribution Of Inflammation To Depression and Fatiguementioning
confidence: 99%
“…The FAS has been validated in healthy cohorts [71]. FAS scores of 10-21 indicate that the patient is "not tired", scores of 22-34 indicate that the patient is "tired", and scores of [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] indicate that the patient is "very tired" [72]. We evaluated the relationship between the biomarkers of inflammation shown in Fig.…”
Section: Inflammation and The Biological Basis Of Psfmentioning
confidence: 99%
“…This hypothesis is informed by a number of observations demonstrating that depressive-like behavior is induced by administration of PICs. Interferon alpha (IFN-α) studies indicated that 28 % of hepatitis C patients developed a new onset major depressive episode during treatment with IFN-α [21]; the rate reported in malignant melanoma patients is 45 % [22]. Treatment with paroxetine prevents depressed mood, anxiety, and cognitive dysfunction, but not neurovegetative symptoms, associated with IFN-α treatment.…”
Section: Inflammation and Depressionmentioning
confidence: 99%
“…Using the Hospital Anxiety and Depression Scale, researchers described prevalence rates ranging from 27% 36 to 72.6% 37 , most likely due to differences in the assessment instruments and procedures. A meta-analysis 38 concluded that the presence of depressive symptoms at the beginning of anti-viral treatment enhances the incidence of major depression episodes during treatment and may have a negative impact on treatment adherence and outcome.…”
Section: Prevalence Of Depressive Symptoms and Harmful Alcohol Usementioning
confidence: 99%